TELAAH ADAB PENUNTUT ILMU DALAM ḤILYATU ṬĀLIB AL-‘ILMI DAN IMPLIKASINYA TERHADAP PEMBELAJARAN PAI - Miftahul Hamdi; Syahidin Syahidin; Mokh Iman Firmansyah (IAIN Sorong, 2022)
Adab is an ornament for a student of knowledge, a student of knowledge who has studied PAI (Islamic Religious Education) which in its sub-material contains material related to adab, has good manners towards himself, his teacher and friends and the surrounding environment, in fact PAI learning should be able to make a student of knowledge have good manners on the contrary, such as the occurrence of a very worrying phenomenon such as the crisis of adab from students of knowledge both to their teachers and friends, one of the cases is how dare a student of knowledge disobey his teacher which occurred in Yogyakarta on February 22 2019 in this case, a student of knowledge dared to fight his teacher because his cellphone was confiscated by his teacher, due to this phenomenon the functions and results of PAI learning can be said to be unsuccessful. The purpose of this study is to describe the adab of a knowledge in the book student of Ḥilyatu Ṭālib Al-‘Ilmi by Shaykh Bakr bin Abdullah Abu Zaid and its implications for PAI learning which is expected to be a solution in an effort to improve the quality of education and form students who have manners in accordance with the Law System. National Education (SISDIKNAS) no. 20 of 2003 which one of the goals is to make humans have noble character. This study uses a qualitative approach to the method of library research (library research). Researchers are the key instrument in research, collecting data using techniques library research. Research data analysis was carried out in the form of data reduction, data presentation/display, and data conclusion/verification. The results of the study show that the adab of theknowledge in the book of student of Ḥilyatu Ṭālib Al-‘Ilmi has implications for PAI learning, especially the material on adab for a student of knowledge.